REVIEW OF SPEED PROFILE OPTIMIZATION METHODS FOR ENERGY EFFICIENCY IN TRAIN - Abdillah, Kusuma; Gunawan , Leonardo Gunawan; Handoko , Yunendar Aryo Handoko (Jurnal Rekayasa Mesin, 2024)
Improving energy efficiency in the transportation system is an important goal in facing the challenges of climate change and limited energy resources. Electric trains are a promising alternative for reducing greenhouse gas emissions and dependence on fossil fuels. Speed profile optimization has been a significant research focus on achieving maximum energy efficiency in electric trains. This paper aims to provide insight into energy efficiency using speed profile optimization.  Several issues were discussed in this paper including energy consumption modeling methods, speed profile optimization methods, and integration of speed profile optimization with schedules and regenerative braking. This study concluded that the most frequently used energy consumption modeling is the deterministic model using the Davis equation. There are two classifications in optimization: classical and modern methods (heuristics). Classical optimization methods are often used on problems with simple constraints, and modern methods are often used on problems with more complex constraints or variables.